1990
DOI: 10.1021/bi00488a042
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria glycolipids as potential pathogenicity effectors: alteration of model and natural membranes

Abstract: Four mycobacterial wall glycolipids were tested for their effects on phospholipidic liposome organization and passive permeability and on oxidative phosphorylation of isolated mitochondria. From fluorescence polarization of diphenylhexatriene performed on liposomes it was concluded that the two trehalose derivatives (dimycoloyltrehalose and polyphthienoyltrehalose) rigidified the fluid state of liposomes, the triglycosyl phenolphthiocerol slightly fluidized the gel state, while the peptidoglycolipid ("apolar" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 18 publications
5
46
0
Order By: Relevance
“…Our results revealed that an as-yet-uncharacterized gene adjacent to putative hydrolase and carboxylase genes is involved in lipid metabolism. We concluded that the lipid moiety missing in the P1 mutant participates in impeding PM, as previous reports have shown that mycobacterial lipids can modify membranes (35) and also prevent actin nucleation, which is necessary for PM (1).…”
Section: Discussionsupporting
confidence: 65%
“…Our results revealed that an as-yet-uncharacterized gene adjacent to putative hydrolase and carboxylase genes is involved in lipid metabolism. We concluded that the lipid moiety missing in the P1 mutant participates in impeding PM, as previous reports have shown that mycobacterial lipids can modify membranes (35) and also prevent actin nucleation, which is necessary for PM (1).…”
Section: Discussionsupporting
confidence: 65%
“…GPLs from M. avium, essentially through its lipopeptide fragment, have been reported to disturb cell membrane ultrastructure and to change the expression of surface receptors of murine macrophages (43). In addition, mycobacterial GPLs are able to get inserted into phospholipid monolayers (44) and to disturb its properties (45). Such an insertion of molecules may alter interactions of mycobacteria with their host cell.…”
Section: Discussionmentioning
confidence: 99%
“…PGLs have been shown to inhibit the lymphoproliferative response (26,44), to suppress monocyte oxidative responses (56), and to scavenge oxygen radicals (47). Similarly, GPLs, which are mainly the most simple version of these molecules, have been shown to inhibit both the nonspecific mitogen-induced proliferation of mononuclear cells (10) and mitochondrial oxidative phosphorylation (55). Keeping in mind that bacterial pathogenicity and virulence are multifactorial, it is not surprising that some nonpathogenic mycobacterial species, like M. gastri, synthesize PGLs (15, 57), whereas both virulent smooth transparent and avirulent smooth opaque strains of M. avium-M. intracellulare elaborate GPLs (5), as does the nonpathogenic M. smegmatis (17), while some virulent strains are devoid of these glycolipids (15,18,53).…”
Section: Vol 178 1996 Surface-exposed Lipids On Mycobacterial Cell mentioning
confidence: 99%